THE EFFECT OF ANALOGS OF ANGIOTENSIN-II ON DRINKING AND CARDIOVASCULAR-RESPONSES TO CENTRAL ANGIOTENSIN-II IN THE RAT - Camargo, LAA; Deluca, L. A.; Menani, José Vanderlei [UNESP]; Renzi, Antonio [UNESP]; Saad, W. A.; Silveira, JEN (Cambridge University Press, 1991)
1. Intracerebroventricular (I.C.V.) infusion (60 ng h-1) of Isoleu5-angiotensin II (Isoleu5-AngII) and des-amine-angiotensin II (des-amine-AngII) in rats caused increased drinking behaviour and an increase in arterial blood pressure.2. Des-amine-AngII caused similar increases in heart rate and arterial blood pressure as AngII.3. Previous I.C.V. injection of the antagonists [Leu8]-AngII, des-amine-[Leu8]-AngII and octanoyl-[Leu8]-AngII prevented the increases in heart rate and blood pressure produced by I.C.V. infusion of AngII and caused partial reduction of the dipsogenic response.4. The three antagonists had no effect on the increase in arterial blood pressure and heart rate caused by des-amine-AngII. The drinking response was reduced by previous injection of [Leu8]-AngII and des-amine-[Leu8]-AngII but not by octanoyl-[Leu8]-AngII.5. In conclusion, Isoleu5-AngII and des-amine-AngII increase drinking behaviour, arterial blood pressure and heart rate when infused into the cerebral ventricle of rats. The study with the antagonists showed that des-amine-AngII probably binds more strongly to AngII-receptors.